Ecology of the gemsbok Oryx gazella gazella (Linnaeus) and blue wildebeest Connochaetes taurinus (Burchell) in the southern Kalahari - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2013)
Thesis (PhD (Zoology))--University of Pretoria, 2008.